1997
DOI: 10.1007/bf02466519
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of chromatographic separations by use of a chromatographic response function, empirical modelling and multivariate analysis

Abstract: SummaryThe chiral separation of the drug substance R,Soxybutynin chloride on a reversed phase HPLC system has been optimised by use of empirical modelling and multivariate analysis. The separation was characterised by a new chromatographic response function developed to modulate both quality of separation and retention time. The study includes a comparison between three different multivariate techniques (multi-layer feed-forward neural networks, multiple linear regression and partial least squares regression) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 15 publications
0
12
0
2
Order By: Relevance
“…I mix = (J mix /J std )I std (8) where I mix and I std are the concentrations of the analytes in the mixtures and the standard samples, respectively; J mix and J std are the corresponding peak areas.…”
Section: Description Of the Als Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…I mix = (J mix /J std )I std (8) where I mix and I std are the concentrations of the analytes in the mixtures and the standard samples, respectively; J mix and J std are the corresponding peak areas.…”
Section: Description Of the Als Methodsmentioning
confidence: 99%
“…When physical separation of sample components is not fully accomplished, quantification difficulties stemming from poorly resolved peaks may still be overcome mathematically using chemometrics [3]. Chemometrics methods have been used in liquid chromatography and other separation techniques to check peak purities [4][5][6], to improve the resolution and quantification [7], and to optimize the separation conditions [8][9][10]. As the applications of CE are widespread in many fields of analytical chemistry, more and more chemometrics methods are modified for CE analysis.…”
Section: Introductionmentioning
confidence: 99%
“…To study the linearity of the response, a series of working standard solutions of 5,10,15,20,25,30,35,40,45 and 50 mg mL -1 for haloperidol and of 0.05, 0.10, 0.15, 0.20, 0.25, 0.30, 0.35, 0.40, 0.45 and 0.50 mg mL -1 for each related compound were prepared. The linearity of peak area response vs. concentration was studied.…”
Section: Validation Proceduresmentioning
confidence: 99%
“…The CRF is a coefficient which characterizes the quality of separation in a quantitative manner. Preferably, a flexible function that allows resolution criteria to be specified (15). The corresponding terms in the chromatogram are then compared to these criteria.…”
Section: Optimization Of Separation Of a Mixture Of Haloperidol And Imentioning
confidence: 99%
“…Minimum resolution and maximum retention times are set by the user and the program calculates the optimum by means of a search routine. Jacobsson et al [19] suggested a chromatographic response function (CRF) which modulates both separation quality and retention time for chiral separations. They also used neural network (NN) methods and compared them with MLR and PLS regression.…”
Section: Introductionmentioning
confidence: 99%